Development integrated science learning device on human digestive system material based on inquiry-flipped classroom - Maria Novita Inya Buku; Getrudis Wilhelmina Nau; Imelda Tidora Sombo (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
At Rosa Mystica Catholic Junior High School, networked learning has not been linked to specific learning models and media. Teachers still face difficulties in creating online learning devices. It is necessary to develop learning devices using appropriate learning models and media to assist teachers in learning online. This will positively impact the quality of learning in the network at school. This study aimed to assess the Integrated Science learning device's validity, effectiveness, and practicality based on the inquiry-flipped classroom approach. The study developed learning devices such as syllabus, lesson plans, and electronic student worksheets. The research was conducted in January 2022 at Rosa Mystica Catholic Junior High School. This is a research and development project that uses the ADDIE model. The research findings indicate that the inquiry-based flipped classroom learning device is highly valid, effective, and practical. It is suitable for integrated science learning, specifically the human digestive system. This study contributes to the innovation of integrated science learning, as the combination of inquiry-based and flipped classroom models can create a more effective and engaging learning experience for students.Abstrak. Pembelajaran dalam jaringan yang terjadi di sekolah menengah pertama katolik Rosa Mystica belum terkait dengan model dan media pembelajaran tertentu. Guru masih kesulitan membuat perangkat pembelajaran untuk pembelajaran dalam jaringan. Perlu dilakukan pengembangan perangkat pembelajaran menggunakan model dan media pembelajaran untuk membantu guru dalam melaksanakan proses pembelajaran dalam jaringan yang berdampak pada perbaikan kualitas pembelajaran dalam jaringan di sekolah. Tujuan penelitian ini adalah untuk mengetahui validitas, efektifitas perangkat dan kepraktisan perangkat pembelajaran IPA Terpadu berbasis inkuiri-flipped classroom. Perangkat pembelajaran yang dikembangkan dalam penelitian ini adalah silabus, rencana pelaksanaan pembelajaran dan lembar kerja peserta didik elektronik berbasis model pembelajaran inkuiri-flipped classroom. Penelitian ini dilaksanakan pada bulan Januari tahun 2022 di SMPK Rosa Mystica. Penelitian ini merupakan penelitian dan pengembangan menggunakan model ADDIE. Hasil penelitian ini menunjukkan bahwa perangkat pembelajaran berbasis inkuiri-flipped classroom sangat valid, efektif dan praktis sehingga layak digunakan dalam pembelajaran IPA terpadu materi sistem pencernaan pada manusia. Penelitian ini memberikan kontribusi terhadap inovasi dalam pembelajaran IPA Terpadu, penggabungan model pembelajaran inkuri dan flipped classroom dapat membuat pembelajaran yang lebih efektif dan menarik bagi peserta didik.